Singing Tradition of the Inhabitants of Lithuania Minor from the Second Half of the 20th Century to the Beginning of the 21st Century - Petrošienė, Lina (Tautosakos darbai, 2021)
The article analyses how the folk singing tradition of the Lithuania Minor developed in the late 20th and in the early 21st centuries. It examines the activities of the folklore groups in the Klaipėda Region during the period of 1971–2020, focusing on those that assert fostering of the lietuvininkai singing tradition as their mission or one of their goals. The study employs the previously unused materials, which allow revising the former research results regarding the revival of the Lithuanian ethnic music and show the folklore ensembles working in the Klaipėda Region as a significant part of the Lithuanian folklore movement and the revival of the ethnic music, emerging from the 1960s. Special emphasis is placed on the early phase in adoption of the lietuvininkai singing tradition related to the activities of the folklore ensemble “Vorusnėˮ established in 1971 at the Klaipėda faculties of the State Conservatory of the former LSSR, and the role it had in prompting the creation of other folklore groups in Klaipėda, as well as its impact on the broader cultural and educational processes taking place in the Klaipėda Region. In the 20th century, the prevailing narrative regarding the Lithuanian inhabitants of the Lithuania Minor maintained that books, hymns, schools, church, social and cultural organizations, and choral or theatre activities were the most significant factors influencing the cultural expression of lietuvininkai, while the Lithuanian folklore was hardly practiced anymore or even considered an inappropriate thing. Judging from the folklore recordings, the folk singing tradition supported by the lietuvininkai themselves disappeared along with the singers born in the late 19th century. However, after the WWII, it was adopted and continued by the folklore groups appearing the Klaipėda Region. These groups included people from the other regions of Lithuania who had settled there. This is essentially the process of reviving the ethnic music, which began in Europe during the Enlightenment period and continues in many parts of the world. “Vorusnėˮ was founded in 1971 as the first institutional student folklore ensemble in Klaipėda Region. For 27 years, its leader was a young and talented professor of the Baltic languages Audronė Jakulienė (later Kaukienė). She became the founder of the linguistic school at the Klaipėda University (KU). In the intense and multifaceted activities of the “Vorusnėˮ ensemble, two different stages may be discerned, embracing the periods of 1971–1988 and 1989–2000. In 1971–1988, the ensemble mobilized and educated students in the consciously chosen direction of fostering the Lithuanian ethnic culture, sought contacts with the native lietuvininkai, collected and studied ethnographic and dialectal data, prepared concert programs based on the scholarly, written, and ethnographic sources, gave concerts in Lithuania and abroad, and cooperated with folklore groups from other institutions of higher education. In 1989–2000, the “Vorusnėˮ ensemble engaged in numerous other areas of activity. The children‘s folklore ensemble “Vorusnėlėˮ was established in 1989; both “Vorusnėˮ and “Vorusnėlėˮ became involved in the activities of the community of the Lithuania Minor founded in 1989. The leader of the ensemble and its members contributed to the establishment of the Klaipėda University, which became an important research center of the Prussian history and culture. The leader of the ensemble and her supporters created a new study program of the Lithuanian philology and ethnology at the KU, which during its heyday (2011–2014) had developed three levels of higher education, including bachelor’s, master’s and doctoral studies. The Folklore Laboratory and Archive was established at the Department of the Baltic Linguistics and Ethnology, headed by Kaukienė, and young researchers in philology, ethnology, and ethnomusicology were encouraged to carry out their research there. In the course of over two decades, Kaukienė initiated organizing numerous research conferences dealing with lietuvininkai language and culture. Until 1980, “Vorusnėˮ was the only folklore ensemble in the Klaipėda Region, but in 1985, there were already ten folklore ensembles. These ensembles developed different creative styles that perhaps most notably depended on the personal structure of these ensembles and their leaders’ ideas and professional musical skills. Generally, at the beginning of their activity, all these ensembles sang, played and danced the folklore repertoire comprising all the regions of Lithuania. The activities of “Vorusnėˮ and other folklore ensembles in Klaipėda until 1990 showed that revival of folklore there essentially followed the lines established in other cities and regions of Lithuania. During the first decade after the restoration of independence of Lithuania in 1990, folklore was in high demand. In Klaipėda, the existing ensembles were actively working, and the new ones kept appearing based on the previous ones. The folklore ensembles of the Klaipėda Region clearly declared their priorities, embracing all the contemporary contexts. Some of them associated their repertoire with the folklore of lietuvininkai, others with Samogitian folklore. The lietuvininkai singing tradition was adopted and developed in two main directions. The first one focused on authentic reconstruction, attempting recreation with maximum accuracy of the song‘s dialect, melody, and manner of singing, as well as its relationship to customs, historical events or living environment. The second direction engaged in creative development, including free interpretations of the songs, combining them with other styles and genres of music and literature, and using them for individual compositions. These two ways could be combined as well. Lietuvininkai are not directly involved in these activities, but they tolerate them and participate in these processes in their own historically and culturally determined ways. The contemporary artistic expression of the promoters of the lietuvininkai singing tradition is no longer constrained by the religious and ideological dogmas that were previously maintained in the Lithuania Minor and in a way regulated performance of these songs. It is determined nowadays by consciousness, creativity, resourcefulness, and knowledge of its promoters. The dogmas of the Soviet era and modernity have created a certain publicly displayed (show type) folklore. The ensembles took part of the institutionalized amateur art, subsequently becoming subject to justified and unjustified criticism, which is usually levelled on them by the outsiders studying documents and analyzing processes. However, favorable appreciation and external evaluation by the participants of the activities and the local communities highlight the meaning of this activity.